Currency crisis in Malaysia: the leading indicators / Nur 'Izzati Akmal Kamarul Baharin - Kamarul Baharin, Nur 'Izzati Akmal (2016)
Currency exchanges are considered as one of the important issues and serious concern for this modern era globalization. A country must have a strong and stable currency in order to maintain the capital and finance. Recently, Malaysia get a lot of complain from the citizens who questioned the government in manage the economy that cause such as increase in inflation rate, high interest rates and high government rates and debt. Due to this problem, this research sought to shed lights on factors affecting the changes of currency in Malaysia compared to USD currency and to identify the main factor contribute to this problem. This paper aims at finding out the impact of Macroeconomic Variables toward Malaysia Currency. The variables used in this study are Inflation Rate, Interest Rate, Government Debt and Term of Trade. The methodology used in this study is Multiple Linear Regression Correlation Test with time series that get from Data Stream and World Bank. Hence, the results of this study would give theoretical understanding of complex interactions between macroeconomic fundamentals, investors' expectations and government policy.